Growth and development of \(Eleocharis ochrostachys\) Steud. reproduced from its tubers - Thi Phuong, Vo; Du Sanh, Nguyen (Academia Journal of Biology, 2021)
In this study, the growth and development of Eleocharis ochrostachys were investigated in a control condition. Its tubers of the plant sprouted to produce stems after being cultured in plastic pots for several days. After 120 days, the plant grew to a height of 42.8 cm on average, stem diameters were from 1.5 to 2.0 mm, and the plant started to bloom and produce tubers. The plant spikelet had dimensions of 1.0–2.0 cm high, 2.0–2.5 mm wide after 120 days. The achenes were formed after 128–130 days, had dimensions of 1.15–1.20 mm long, and 0.5–0.7 mm wide when the plant was cultured for 150 days. The tubers had dimensions of 7.0–9.0 mm long, 4.0–6.0 mm diameter, and were about 0.06–0.1 grams after 150 days. This study provided information on the development of Eleocharis ochrostachys cultured in the greenhouse.